Editorial Board and Guideline for the Authors of the TAWARIKH Journal, issue of April 2015 - TAWARIKH, Editor Journal (TAWARIKH, 2015)
TAWARIKH will provide a peer-reviewed forum for the publication of thought-leadership articles, briefings, discussion, applied research, case and comparative studies, expert comment and analysis on the key issues surrounding the history education and historical studies, and its various aspects. Analysis will be practical and rigorous in nature.Bandung, Indonesia: April 28, 2015.Andi SUWIRTAChairperson of ASPENSI (the Association of Indonesian Scholars of History Education) in Bandung, West Java, Indonesia.Â